Detection of free cancer cells in peritoneal cavity in patients surgically treated for gastric adenocarcinoma - Kostić Zoran; Ćuk Vladimir; Bokun Radojka; Ignjatović Dragan; Ušaj-Knežević Slavica; Ignjatović Mile (Vojnosanitetski Pregled)
Bacground/Aim. Peritoneal metastasis is a leading cause of therapeutic failure after an operative treatment of patients with gastric adenocarcinoma. Free cancer cells might induce or indicate an early peritoneal seeding with a subsequent peritoneal metastasis. The aim of this study was to determine the frequency of the presence of free cancer cells in the peritoneal cavity in the patients surgically treated for gastric adenocarcinoma, and its relation to certain clinical, operative and pathohistological parameters. Methods. Inside a period from April 2000, and April 2004, the total of 100 patients underwent intraoperative peritoneal lavage for cytological examination. Immediately after the laparotomy, 200 ml physiologic saline, heated to 37 °C, was introduced into the abdominal cavity, manually dispersed and collected from the region around the gastric tumor and the pouch of Douglas. The nucleated cell layer was smeared on four glass slides for every patient and dyed with May-Grünwald-Giemsa stain. The cytological findings were defined as positive or negative according to the presence of cancer cells. The frequency of positive cytological findings was compared to the location and the diameter of the cancer, pathohistological type of carcinoma, pathohistological stage of the disease, lymph node and the liver and/or peritoneal metastases and the type of surgical procedure. Results. Free cancer cells were found in 24 (24%) of the patients, while in 76 (76%) of them cytological findings were negative. A statistically highly significant difference (p ≤ 0.001) in the frequency of positive cytological finding was found between the groups of patients with and without cancer invasion of serosa, with cancer diameters > 5 cm and ≤ 5 cm, in the stage of disease I, II and III, IV, with macroscopically present and without metastases, with resection and D2 lymphadenectomy and palliative procedure. Free cancer cells were statistically more frequently (p ≤ 0.05) detected in the patients with lymph nodes metastases comparing to the patients without lymph nodes involvement. The results of the univariate analysis showed that the cancer diameter > 5 cm, tumor invasion of serosa, pathohistological stage of the disease III and IV and macroscopically visible metastases were the most important risk factors for the free cancer cells detection. Conclusion. Peritoneal lavage cytology was shown to be a useful tool for the detection of the group of patients with greatest risk of peritoneal dissemination. The frequency of positive cytological findings was highly associated with the diameter of the tumor and the cancer invasion of serosa. Cytological examination of peritoneal lavage fluid improved the accuracy of staging and selection of patients who might have benefit from neoadjuvant chemotherapy.